Microfluidics for electrophysiology, imaging, and behavioral analysis of Hydra. Issue 17 (10th July 2018) - Badhiwala, Krishna N.; Gonzales, Daniel L.; Vercosa, Daniel G.; Avants, Benjamin W.; Robinson, Jacob T.
Abstract : Microfluidic devices allow scalable and customizable solutions for multi-modal interrogation of these soft, deformable Hydra. Abstract : The nervous system of the cnidarian Hydra vulgaris exhibits remarkable regenerative abilities. When cut in two, the bisected tissue reorganizes into fully behaving animals in approximately 48 hours. Furthermore, new animals can reform from aggregates of dissociated cells. Understanding how behaviors are coordinated by this highly plastic nervous system could reveal basic principles of neural circuit dynamics underlying behaviors. However, Hydra's deformable and contractile body makes it difficult to manipulate the local environment while recording neural activity. Here, we present the first microfluidic technologies capable of simultaneous electrical, chemical, and optical interrogation of these soft, deformable organisms. Specifically, we demonstrate devices that can immobilize Hydra for hours-long simultaneous electrical and optical recording, and chemical stimulation of behaviors revealing neural activity during muscle contraction. We further demonstrate quantitative locomotive and behavioral tracking made possible by confining the animal to quasi-two-dimensional micro-arenas. Together, these proof-of-concept devices show that microfluidics provide a platform for scalable, quantitative cnidarian neurobiology. The experiments enabled by this technology may help reveal how highly plastic networks of neurons provide robust control of animal behavior.